RELIGIOUS COPING AND PARENTAL BURNOUT AMONG MOTHERS WORKING AS NURSES IN ACEH PROVINCE, INDONESIA: A CROSS-SECTIONAL STUDY - Febriyani; Amna, Zaujatul; Mirza; Iskandar (Lembaga Penelitian dan Terapan untuk Kesehatan Jiwa (Lenterakaji), 2025)
Background: mothers who are employed as nurses encounter dual responsibilities, entailing both onerous workloads in medical facilities and demanding parenting duties in their homes. This dual burden has been shown to heighten the risk of parental burnout. Parental burnout, defined as emotional and physical exhaustion in parenting, has the potential to adversely impact parent-child relationships and child development. One approach to coping with this condition is through religious coping, which involves relying on religious beliefs and practices to manage life's difficulties. Purpose: To examine the relationship between religious coping and parental burnout among mothers working as nurses in Aceh. Methods: Quantitative correlational approach was employed with 173 nurse mothers selected using purposive sampling. Data were gathered using the Iranian Religious Coping Scale and the Parental Burnout Assessment. Results: The result of the study indicated that there was no significant relationship between religious coping and parental burnout. Despite the elevated levels of religious coping exhibited by the participants, particularly through practices such as prayer and salat, there was an absence of indications suggesting parental burnout. Conclusion: While religious coping may offer a mechanism for managing general stress, it is not sufficient to address the complex and multidimensional challenges associated with parental burnout. However, a study of nurse mothers in Aceh revealed that those who exhibited high levels of religious coping did not experience parental burnout. Abstrak Latar Belakang: Ibu yang bekerja sebagai perawat menghadapi tanggung jawab ganda yaitu beban kerja yang tinggi di rumah sakit dan tugas mengasuh anak di rumah, yang meningkatkan risiko mengalami parental burnout. Parental burnout merupakan kondisi kelelahan emosional dan fisik dalam menjalani peran sebagai orang tua, yang dapat berdampak negatif pada hubungan orang tua dan anak serta perkembangan anak. Salah satu pendekatan untuk mengatasi kondisi ini adalah coping religius, yaitu mengandalkan keyakinan dan praktik keagamaan untuk menghadapi kesulitan hidup. Tujuan: Untuk mengetahui hubungan antara coping religius dengan parental burnout pada ibu yang bekerja sebagai perawat di Aceh. Metode: Menggunakan pendekatan kuantitatif korelasional dengan jumlah sampel sebanyak 173 ibu yang bekerja sebagai perawat, dipilih melalui teknik purposive sampling. Pengumpulan data dilakukan menggunakan Iranian Religious Coping Scale dan Parental Burnout Assessment. Hasil: Hasil penelitian menunjukkan tidak ada hubungan yang signifikan antara coping religius dan parental burnout. Meskipun tingkat coping religius yang tinggi ditemukan terutama melalui salat dan doa, partisipan tidak menunjukkan tanda-tanda parental burnout. Kesimpulan: Coping religius dapat membantu dalam mengelola stres umum, namun belum cukup kuat mengatasi tantangan parental burnout yang kompleks dan multidimensional.